2016
DOI: 10.1152/japplphysiol.00033.2016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypervolemia by protein and glucose supplementation during aerobic training on thermal and arterial pressure regulations in hypertensive older men

Abstract: In Japan, the incidence of heat illness in older people has rapidly increased during midsummer in the last decade, and we suggested that whey-protein+carbohydrate supplementation during aerobic training would increased plasma volume (PV) to enhance thermoregulatory adaptation in older men ( J Appl Physiol 107: 725-733, 2009); however, >60% of people age 65 and older suffer from hypertension, and the symptoms may be worsened by hypervolemia. To examine this, we randomly divided 21 older men (∼69 yr) with ∼16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 36 publications
2
24
0
Order By: Relevance
“…Additionally, milk protein (10–12 g) and carbohydrate (15–35 g) supplementation immediately after exercise was reported to enhance plasma volume expansion and, thereby, facilitate thermoregulatory adaptation in older men [19, 20]. Thus, the timely supplementation of adequate amounts of milk protein and carbohydrate might improve age-associated deterioration in homeostatic regulation by providing tissues with required substrates after exercise.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, milk protein (10–12 g) and carbohydrate (15–35 g) supplementation immediately after exercise was reported to enhance plasma volume expansion and, thereby, facilitate thermoregulatory adaptation in older men [19, 20]. Thus, the timely supplementation of adequate amounts of milk protein and carbohydrate might improve age-associated deterioration in homeostatic regulation by providing tissues with required substrates after exercise.…”
Section: Methodsmentioning
confidence: 99%
“…However, rehabilitation therapy in the present study might not retain the loss completely, even we started it early. To compensate this dysfunction in CABG patients, the other strategy is needed to expand body fluid before CABG, which can be achieved by endurance training with protein supplementation [44].…”
Section: Limitationsmentioning
confidence: 99%
“…Consequently, the improved PV expansion response induced by exercise along with post-exercise protein and CHO intake enhances the attenuated increase in cardiovascular and thermoregulatory capacity in elderly individuals compared with young counterparts. Recently, Kataoka et al [90] reported the similar results in hypertensive elderly individuals (∼160 mmHg for systolic and ∼90 mmHg for diastolic blood pressure at rest) that PV and SkBF response to increased T es both increased after aerobic training (60-75% of VO 2 peak for 60 min/day, 3 days/week, for 8 weeks) with protein (10 g) and CHO (15 g) supplementation. Furthermore, they showed that despite the increased PV, arterial blood pressures rather decreased after training with an increased carotid arterial compliance and baroreflex sensitivity.…”
Section: Diabetes and Its Complicationsmentioning
confidence: 65%